PENGARUH BERBAGAI MACAM PANJANG STEK TERHADAP PERTUMBUHAN BIBIT ANGGUR (Vitis vinivera L.) - Kurniastuti, Tri (JURNAL AGRI-TEK, 2016)
This study aims to determine the length of the cuttings are best for growing grape seeds. This research was conducted at the experimental station of Agriculture Faculty of Islamic University Balitar Blitar in September 2015 to November 2015. This study used a randomized block design (RAK) with seven treatments, the cuttings are terdidi length of A = 10 cm, B = 12.5 cm , C = 15 cm, D = 17.5 cm, D = 17.5 cm, 20 cm E = F = G = 22.5 cm and 25 cm and 3 replicates, obtained 21 experimental unit. Data analysis was performed using F test showed significant differences If then tested further by using Duncan’s test at 5% level. The results showed that the length of cuttings significantly affect the percentage of cuttings grow, the time appears buds, percentage of cuttings sprouted buds shoot length, number and length of root cuttings of wine. The growth of seedlings cuttings of the best wines on the length of cuttings 20 cm at the variable percentage of cuttings grow, sprout cuttings percentage, shoot length and root length.Keywords: long cuttings, growing, grape seed